Effective treatment options in amoebic liver abscess in a tertiary care setting in West Bengal: an observational study, India - Mondal, Ankan; Lahiri, Arista; Ray, Prama; Bhattacharjee, Atanu (International Surgery Journal, 2018)
Background: Conservative management and image guided drainage have emerged as mainstay of the treatment in Amoebic Liver Abscess (ALA), with surgery used in complicated cases. The current study was conducted with an objective to demonstrate the effectiveness of the different treatment options in ALA. Methods: An observational study was conducted on 100 patients, aged 19 to 60 years, admitted with sonographic evidence of Amoebic Liver Abscess (ALA) in the General Surgery wards of a tertiary care hospital in Kolkata. Patients coming for regular follow-up after completing treatment were included. On completion of the treatment before discharge a repeat ultrasonography of the upper abdomen was done to confirm remission. Results: Majority of the patients were male, Muslim, rural resident and within 30 – 40 years age. Chief complaints were pain (100%), fever (60%) and abdominal swelling (80%). Tender hepatomegaly (80%) and icterus (36%) were present. Majority patients had the left lobe of the liver affected (72%) and abscess dimension <6 cms (66.67%). Out of the participants with unruptured abscess 21.87% had multiple abscesses. Out of 64 patients subjected to conservative therapy, 44 were successfully managed. Success rate of 72.73% was observed among 44 patients receiving ultrasound guided needle aspiration. All twenty patients subjected for pigtail catheter drainage were cured. Four patients underwent laparotomy and open drainage following intraperitoneal rupture. Conclusions: Conservative treatment was observed to be sufficient in majority of cases of amoebic liver abscess of lesser size with percutaneous catheter drainage useful in large abscess. Surgical intervention was required in ruptured or complicated abscesses.